Evaluation of viscoelastic parameters and photo-based assessment of newly developed dermal substitutes modified with thermostabilized fibroblast growth factor 2 - Knoz, Martin; Holoubek, Jakub; Lipový, Břetislav; Faldyna, Martin; Chaloupková, Radka; Pavliňáková, Veronika; Muchová, Johana; Kacvinská, Katarína; Brtníková, Jana; Jarkovský, Jiří; Vojtová, Lucy (Burns, 2024)
BACKGROUND: The purpose of dermal substitutes is to mimic the basic properties of the extracellular matrix of human skin. The application of dermal substitutes to the defect reduces the formation of hypertrophic scars and improves the scar quality. This study aims to develop an original dermal substitute enriched with stable fibroblast growth factor 2 (FGF2-STAB®) and test it in an animal model. METHODS: Dermal substitutes based on collagen/chitosan scaffolds or collagen/chitosan scaffolds with nanofibrous layer were prepared and enriched with FGF2-STAB® at concentrations of 0, 0.1, 1.0, and 10.0 µg ‧ cm-2. The performance of these dermal substitutes was tested in vivo on artificially formed skin defects in female swine. The outcomes were evaluated using cutometry at 3 and 6 months. In addition, visual appearance was assessed based on photos of the scars at 1-month, 3-month and 6-month follow-ups using Yeong scale and Visual Analog Scale. RESULTS: The dermal substitute was fully integrated into all defects and all wounds healed successfully. FGF2-STAB®-enriched matrices yielded better results in cutometry compared to scaffolds without FGF2. Visual evaluation at 1, 3, and 6 months follow-ups detected no significant differences among groups. The FGF2-STAB® effectiveness in improving the elasticity of scar tissues was confirmed in the swine model. This effect was independently observed in the scaffolds with nanofibres as well as in the scaffolds without nanofibres. CONCLUSION: The formation of scars with the best elasticity was exhibited by addition 1.0 µg ‧ cm-2of FGF2-STAB® into the scaffolds, although it had no significant effect on visual appearance at longer follow-ups. This study creates the basis for further translational studies of the developed product and its progression into the clinical phase of the research.
Keywords: hojení ran; Chitosan; jizva hypertrofická; Cutometry; Fibroblast Growth Factor 2; viskozita; Burns; Visual assessment; Skin, Artificial; Female; kůže; Tissue Scaffolds; Viscosity; popálení; Nanofibers; kolagen; zvířata; Collagen; Wound Healing; Cicatrix, Hypertrophic; Swine; pružnost; ženské pohlaví; tkáňové podpůrné struktury; nanovlákna; Fibroblast grow factor 2; Dermal substitute; Elasticity; umělá kůže; Animals; fibroblastový růstový faktor 2; Animal experiment; chitosan; Disease Models, Animal; prasata; Skin; Scar; modely nemocí na zvířatech